The Future of Cognitive Neuroscience - Aini Ismafairus, Binti Abd Hamid; Jafri Malin, Bin Abdullah; Norsiah, Binti Fauzan (Science Publishing Corporation, 2018)
Cognitive neuroscience is an interdisciplinary area focusing on the application of neuroscience knowledge in areas such as neuroimaging studies, computer science, psychology, marketing, business, general and special education, social sciences, engineering, biology, learning science, health, etcetra. It is a new emerging field that may help Malaysia in the move towards 2050 for the development of economic, improve levels of knowledge and education, intensify healthcare, enhance people’s well-being and expand network collaboration. Academicians, scientists, industry and educators must concentrate on the application cognitive neuroscience in their field of studies. There is a lack of neuroscientists in these fields, and concentrated efforts must come from the top down as well as the bottom up. We need to bring brain and mind sciences and neuroscience to a reputable level that will improve physical and mental health and increase creativity and innovation in Malaysia: A national institute to amalgamate the creative and innovative mind, behaviour, and brain sciences and neuroscience must be established.